Clusters of Adolescent and Young Adult Thyroid Cancer in Florida Counties. (28th April 2014) - Amin, Raid; Burns, James J.
Abstract : Background . Thyroid cancer is a common cancer in adolescents and young adults ranking 4th in frequency. Thyroid cancer has captured the interest of epidemiologists because of its strong association to environmental factors. The goal of this study is to identify thyroid cancer clusters in Florida for the period 2000–2008. This will guide further discovery of potential risk factors within areas of the cluster compared to areas not in cluster. Methods . Thyroid cancer cases for ages 15–39 were obtained from the Florida Cancer Data System. Next, using the purely spatial Poisson analysis function in SaTScan, the geographic distribution of thyroid cancer cases by county was assessed for clusters. The reference population was obtained from the Census Bureau 2010, which enabled controlling for population age, sex, and race. Results . Two statistically significant clusters of thyroid cancer clusters were found in Florida: one in southern Florida (SF) (relative risk of 1.26; P value of <0.001) and the other in northwestern Florida (NWF) (relative risk of 1.71; P value of 0.012). These clusters persisted after controlling for demographics including sex, age, race. Conclusion . In summary, we found evidence of thyroid cancer clustering in South Florida and North West Florida for adolescents and young adult.